DNA methylation and gene expression of immune cell markers in adolescents with chronic cannabis use: an exploratory study - Plank, Anne-Christine; Wiedmann, Melina; Kuitunen-Paul, Sören; Wagner, Wolfgang; Perez-Correa, Juan Felipe; Franzen, Julia; Ioannidis, Charalampos; Mirtschink, Peter; Roessner, Veit; Golub, Yulia (BMC Psychiatry, 2024)
BACKGROUND: Experimental studies indicate that phytocannabinoids have immune-modulatory properties. However, the effects of chronic cannabis use (CCU) in adolescents on their immune cells have been scarcely investigated to date, although CCU is increasingly observed in this age group. METHODS: In this study, we analyzed DNA methylation and gene expression of immune cell markers in whole-blood samples of adolescent CCU-outpatients and non-cannabis-using (NCU) controls (n = 14 vs. n = 15, mean age = 16.1 ± 1.3 years). Site-specific DNA methylation values were used to calculate A) proportion estimates of circulating white blood cell (WBC) types and B) mean DNA methylation values of common immune cell markers (CD4, CD8A, CD19, FCGR3A, CD14, FUT4, MPO), whose gene expression levels were additionally determined. RESULTS: CCU adolescents had a lower estimated proportion of B cells compared to NCU subjects. An originally observed higher proportion of granulocytes in CCU subjects, however, was attenuated when controlling for past-year tobacco use. The observed differences in mean DNA methylation and gene expression of immune cell markers were not statistically significant. CONCLUSION: The results of our explorative study indicate that CCU in adolescents is associated with altered levels of circulating WBCs. Further studies with larger cohorts are warranted to confirm our findings and to provide insights regarding their functional consequences.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Adolescents; B cells; Chronic cannabis use; DNA methylation; Gene expression; White blood cells